2005
DOI: 10.1093/jmedent/42.5.850
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferiSensu Stricto in Yellow-Necked Mice and FeedingIxodes ricinusTicks in a Forest Habitat of West Central Poland

Abstract: Wild rodents and the subadult Ixodes ricinus (L.) ticks infesting them were examined for the presence of Borrelia burgdorferi Johnson, Schmid, Hyde, Steigerwalt & Brenner s.l. in a sylvatic habitat in west central Poland during May-September 2002. In total, 818 feeding ticks were recovered from 73 infested yellow-necked mice, Apodemus flavicollis Melchior; in addition, bank voles, Clethrionomys glareolus Schreber, were rarely captured and proved to be weakly parasitized. Only 2.7% of A. flavicollis and 2.2% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In the two selected rural forest sites (III-IV), large mammals are also major hosts, though medium and small mammals and lizards also play significant roles. The results obtained in this and other studies suggest that the assumption that the immature stages of I. ricinus feed on small- and medium-sized mammals and that imago feed on large mammals (Kurtenbach et al 1995 ; Liz et al 2000 ; Hanincová et al 2003a ; Rizzoli et al 2004 ; Michalik et al 2005 ) should be verified. Thus, all stages of I. ricinus feed on roe deer (Kiffner et al 2010 ), red deer and wild boars.…”
Section: Discussionmentioning
confidence: 50%
“…In the two selected rural forest sites (III-IV), large mammals are also major hosts, though medium and small mammals and lizards also play significant roles. The results obtained in this and other studies suggest that the assumption that the immature stages of I. ricinus feed on small- and medium-sized mammals and that imago feed on large mammals (Kurtenbach et al 1995 ; Liz et al 2000 ; Hanincová et al 2003a ; Rizzoli et al 2004 ; Michalik et al 2005 ) should be verified. Thus, all stages of I. ricinus feed on roe deer (Kiffner et al 2010 ), red deer and wild boars.…”
Section: Discussionmentioning
confidence: 50%
“…Similar prevalence rates were found in A. agrarius from Croatia (1.9%) and in A. flavicollis (1.5%). Studies from Hungary, Lithuania and Poland reported a slightly higher prevalence in A. agrarius and A. flavicollis [8, 3032]. However, we consider that the inter-country comparison of prevalence is meaningless in this context, since the conditions of parasitism by ticks were different, as well as the environment and the period of the year for the surveys.…”
Section: Discussionmentioning
confidence: 89%
“…Without showing distinct preferences, this spirochete genospecies infects two most important reservoir groups, i.e. small rodents and passerine birds [ 36 - 40 ].…”
Section: Discussionmentioning
confidence: 99%